2017
DOI: 10.1016/j.jes.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the removal of fluoroquinolones in activated sludge process: Sorption and biodegradation characteristics

Abstract: The detailed sorption steps and biodegradation characteristics of fluoroquinolones (FQs) including ciprofloxacin, enrofloxacin, lomefloxacin, norfloxacin, and ofloxacin were investigated through batch experiments. The results indicate that FQs at a total concentration of 500μg/L caused little inhibition of sludge bioactivity. Sorption was the primary removal pathway of FQs in the activated sludge process, followed by biodegradation, while hydrolysis and volatilization were negligible. FQ sorption on activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…These authors indicated that higher mixed liquor suspended solids (15 000 mg L –1 ) increased quinolone removal efficiency, mainly by sorption processes. Wang et al assessed the removal of several fluoroquinolone compounds including ciprofloxacin in a laboratory‐scale sequencing batch reactor with an aerobic suspended growth. After 50 h of reaction, the overall removal was 78–91%, indicating that the sorption process is the primary removal pathway for fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%
“…These authors indicated that higher mixed liquor suspended solids (15 000 mg L –1 ) increased quinolone removal efficiency, mainly by sorption processes. Wang et al assessed the removal of several fluoroquinolone compounds including ciprofloxacin in a laboratory‐scale sequencing batch reactor with an aerobic suspended growth. After 50 h of reaction, the overall removal was 78–91%, indicating that the sorption process is the primary removal pathway for fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%
“…After sterilization by autoclaving, the fluoroquinolone concentrations tended to increase, particularly for activated sludge (up to 10 times) indicating a release of the antibiotics from the solid fraction to the liquid fraction. Lindberg et al [26] and Wang et al [27] also found the tendency of norfloxacin to be accumulated in sludge particles. While the negative values of the log octanol-water partitioning coefficient (logK ow ) of the examined quinolones in the literature (e.g.…”
Section: Antibiotic Concentration In the Wastewatermentioning
confidence: 94%
“…On the other hand, at this pH range, the fluoroquinolones are positively charged or neutral because the fluoroquinolones first pK a value and the isoelectric point are between this pH range [27]. In this pH range, zwitterions of the fluoroquinolones have been found to have the strongest affinity to sludge particles than either the cation or anion, thus contributing the largest portion of chemical species adsorbed in the sludge [27].…”
Section: Antibiotic Concentration In the Wastewatermentioning
confidence: 97%
See 2 more Smart Citations